2004
DOI: 10.1016/j.amjhyper.2003.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antihypertensive therapy with the combination of olmesartan medoxomil and hydrochlorothiazide

Abstract: Olmesartan medoxomil/HCTZ combination therapy produced BP reductions of up to 26.8/21.9 mm Hg and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 38 publications
9
106
0
2
Order By: Relevance
“…Our present results show that HCTZ monotherapy induced a greater antihypertensive effect than did LOS monotherapy in DS rats and that combination therapy with both drugs also elicited a greater reduction in blood pressure compared with LOS alone, consistent with previous observations. 31 However, the combination therapy did not result in a decrease in blood pressure greater than that induced by HCTZ monotherapy. One possible explanation for this lack of an additional hypotensive effect is that the dose of HCTZ administered resulted in a near maximal reduction in blood pressure in DS rats, so that the addition of LOS had no further effect.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our present results show that HCTZ monotherapy induced a greater antihypertensive effect than did LOS monotherapy in DS rats and that combination therapy with both drugs also elicited a greater reduction in blood pressure compared with LOS alone, consistent with previous observations. 31 However, the combination therapy did not result in a decrease in blood pressure greater than that induced by HCTZ monotherapy. One possible explanation for this lack of an additional hypotensive effect is that the dose of HCTZ administered resulted in a near maximal reduction in blood pressure in DS rats, so that the addition of LOS had no further effect.…”
Section: Discussionmentioning
confidence: 90%
“…Another possibility is that this dose of HCTZ did not activate the systemic renin-angiotensin-aldosterone system (RAAS) in the presence of severe salt loading. 31 Loop diuretics such as furosemide, at excessive doses, induce a contraction of intravascular volume, the hemodynamic signal for RAAS activation, as well as a reduction in the production of compensatory natriuretic peptides. Low doses of thiazide diuretics such as HCTZ have been effectively and safely used for the treatment of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…All combinations with the angiotensin receptor blockers were developed initially with HCTZ at a dose of 12.5 mg; these combinations typically show additive effects on blood pressure lowering regardless of which angiotensin receptor blocker was evaluated. 6,[19][20][21][22][23][24] Incremental BP-lowering effects have been observed with larger doses of hydrochlorothiazide, that is, 25 mg, in combination with the angiotensin receptor blockers, 6,19 which led to the development of the fixed-dose combination formulations used in our trial. In an earlier study by Benz and coworkers, 19 valsartan-HCTZ at a dose of 160/25 mg lowered the BP by 22/15 mm Hg compared with 18/ 14 mm Hg for valsartan-HCTZ at a dose of 160/ 12.5 mg. Trenkwalder et al 25 also showed that patients not controlled on valsartan-HCTZ 160/ 12.5 mg had an additional 8.4/8.3 mm Hg reduction in BP when the diuretic dose was increased to 25 mg.…”
Section: Principal Findingsmentioning
confidence: 99%
“…The antihypertensive efficacy of olmesartan medoxomil alone and in combination with HCTZ was studied by Chrysant et al 9 in a factorial design study in 502 hypertensive patients with MSDBP X100 and p115 mm Hg. In this study, olmesartan medoxomil 10, 20 or 40 mg/day alone and in combination with HCTZ 12.5 and 25.0 mg/day were used.…”
Section: Combination Treatmentmentioning
confidence: 99%
“…In several randomised placebo-controlled studies, olmesartan medoxomil has demonstrated significant antihypertensive effects compared to placebo. 1,2 In other comparative studies, olmesartan medoxomil showed similar blood pressure (BP) lowering efficacy with angiotensin converting enzyme (ACE) inhibitors, calcium channel blockers, b-blockers and diuretics, [3][4][5][6][7][8][9] but superior antihypertensive potency against other ARBs given in equivalent starting doses. [10][11][12][13] In other studies, olmesartan medoxomil given in the highest recommended daily doses, its antihypertensive effect was similar to other ARBs.…”
Section: Introductionmentioning
confidence: 98%